Critical appraisal of Published Clinical Trials on "The Effect of Complementary and Alternative Medicine on Infertile Women's Pregnancy Rate" - Farangis Sharifi; Maryam Kabardian; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2021)
Introduction: Randomize controlled trials (RCTs) are important in evidence-based medicine, and treatment decisions are made based on the results of these studies. Due to the frequency of this type of research on complementary and alternative medicine (CAM) and its effect on infertility, this study was performed with aim of critical appraisal of the effect of CAM on infertile women's pregnancy rate. Methods: In this critical review, searching was made on electronic scientific databases including Scopus, PubMed, Embase, Web of Science, SID and Magiran without time limitation until November 2020 using the keywords of CAM and infertility. Inclusion criteria was Persian or English published RCTs related to the use of CAM in infertile women and exclusion criteria was lack of access to the full text of the article and non-compliance of the study method with the principles of RCTs. In the evaluation of the articles, the 2017 CONSORT checklist was used for non-pharmacological treatments. The scoring range was 0-44. Results: Out of the 25 articles reviewed, the overall quality compliance rate with the CONSORT checklist was estimated about 50%. The greatest weakness in reporting was observed in the title and abstract (0.88 ± 0. 726) and the discussion section (1.16 ± 0.898). The total mean score of the articles was 22.68 ± 6.176 with a minimum of 9 and a maximum of 33. Conclusion: The appraised articles in the present study had an average quality. It is required that RCTs be conducted and reported in accordance with standard principles and be thoroughly reviewed critically with relevant checklists before publication. Training of researchers helps improving the quality of articles.